Social Skill Training for Socially Isolated Patients: Concept Analysis - Suhermi Suhermi; Siti Linda Ariska; Asmi Asmi; Ika Aditya Wirawan; Edy Surya Pratama; Satriya Pranata; Siti Aisah; Aric Vranada (Indonesian Journal of Global Health Research, 2024)
Patients with social isolation are often found in psychiatric nursing practice, especially those with mental disorders such as schizophrenia, depression, or social anxiety disorder. Social isolation is someone who avoids social interaction and has difficulty communicating or building significant relationships with others. This condition greatly affects the patient's quality of life and worsens the symptoms of mental disorders experienced. The purpose of this concept analysis is to gain a more detailed and in-depth understanding of Social Skill Training in Socially Isolated Patients.This concept analysis uses the Walker and Avant approach with analysis steps including: utilization of attributes in case models, borderline cases, related cases, and opposite cases, explaining antecedents and consequences. Relevant literature findings related to the concept were obtained through concept databases such as Google Scholar, PubMed, Scopus, Science Direct, NCBI, Researchgate, Publish and Perish and ProQuest. Keywords used in the literature search include "Social Skill Training", "Social Isolation", and "Scizophrenia". The inclusion criteria for articles were articles written in English and Indonesian, full text, and articles published in the last 5 years from 2019 - 2024 and open access.The results Social Skill Training(SST) is effective in improving social skills, reducing symptoms of social isolation, and improving the quality of life of patients with mental health disorders. In the context of social isolation, SST provides a structured approach to help patients develop communication skills, manage emotions, and increase their confidence in social interactions..It is expected Nurses should use SST as a standard intervention in treating patients with social isolation, especially those caused by mental disorders such as schizophrenia, depression, and social anxiety.